Genetic profiles of different ethnicities living in Karachi as regards to tobacco-metabolizing enzyme systems and the risk of oral cancer - Muhammad Mohiuddin Alamgir; Qamar Jamal; Talat Mirza (Journal of the Pakistan Medical Association, 2022)
Objective: To detect polymorphisms of CYP1A1, GSTM1 and GSTT1 gene loci among various tobacco-consuming ethnicities in an urban centre, and to relate these with susceptibility to oral cancer. Method: The cross-sectional, case-control study was conducted at Ziauddin University, Karachi, and the Dow University of Health Sciences, Karachi, from 2011 to 2016, and comprised patients having oral squamous cell carcinoma in group A, with oral precancerous lesions in group B, and tobacco habit-matched controls in group C. Routine histopathology was followed by molecular analysis through polymerase chain reaction and polymerase chain reaction-restriction fragment length polymorphism techniques. Data was analysed using SPSS 20. Results: Of the 358 subjects, 150(42%) were in group A, 100(28%) in group B, and 108(30%) in group C. There were 190(53.1%) Urdu-speaking subjects, 42(11.7%) Memoni-speaking, 37(10.3%) Sindhi-speaking, 34(9.5%) Balochi-speaking, 25(7%) Pashto-speaking, 15(4.2%) Punjabi-speaking, and 15(4.2) of other ethnicities. Among the Urdu-speaking ethnicity, CYP1A1 MspI heterozygous variant was the most prevalent genotype ingroup A 50(66.7%), group B 37(62.7%) and group C 36(64.3%). The homozygous variant was equally distributed in group A 8(13.5%) and group B 10(13.3%), while it remained quite low in group C 4(7.1%). Homozygous genotype was most common in Pashto-speaking subjects in group A 4(57.1%). In Urdu-speaking subjects, GSTM1-null genotype was mostly found in group B 19(32.2%), while GSTT1-null genotype was most common in group A 12(16%). Other than Urdu-speaking, GSTM1-null variant was most frequent in Sindhi-speaking subjects in group 2 8(80%). ---Continue